Model-Based Family Health Promotion To Improve The Quality Of Life Of Children Aged 2-4 Years - Heni Puji Wahyuningsih; Siti Tyastuti (Pusat Unggulan Iptek (PUI) Poltekkes Kemenkes Yogyakarta, 2020)
Children aged 2-4 years are a golden period as a basis for the next development. Because the primary care role of children under five is by families, it is necessary to do family-based health promotion. Model health promotion information-motivation-behavioral skills s implemented in the form of family assistance activities. Namely the family assistance model by providing information, motivation, and examples of behavioral skills in parenting children under five. The purpose of this research is knowing the effectiveness family-based model of health promotion models in formation-motivation-behavioral (IMB) skill s to the quality of life for toddlers 2-5 years. Pure design experiment using Randomized Controlled Trial with pre-post test with a single-blind control group. The research subjects are toddlers aged 2-4 years many 60, who meet the criteria have significant congenital abnormalities and not multiple. The instrument of this study is a Guide to family-based health promotion models, with the research instrument being the Pediatric Quality of Life Inventory (PedsQL ™) Questionnaire. The health promotion model of information-motivation-behavioral skills (IMB) is carried out in the form of family mentoring activities to improve the quality of life of children aged 2-4 years ( p-value0,000). The average enhancement child's quality of life score, more large ( mean difference 16.90, p-value 0,000 ) in the group experiment ( IMB Model ) compared the control group. External variables that affect the quality of life of children aged 2-4 years are income and parenting parents.